Effects of exercise on serum ischemia-modified albumin, brain natriuretic peptide and copeptin levels in boxers and kick boxers - Memmedov, Hikmet; Bakan, Ebubekir; Öztürk, Nurinnisa; Baygutalp, Nurcan Kılıç; Kaynar, Ömer; Gül, Mehmet Ali; Yazıcı, Ahmet Gökhan (African Field Epidemiology Network-Afenet, 2022)
Introduction: boxing and kick boxing are combat sports that can cause severe head, neck, face and hand injuries during fighting. Then, traumatic brain injury (TBI) incidence is high in these sports. Ischemia-modified albumin (IMA), brain natriuretic peptide (BNP) and copeptin have diagnostic and prognostic value for cardiac and non-cardiac ischemic events. The purpose of this study is to evaluate exercise-induced variations of serum IMA, BNP and copeptin. Methods: twenty male boxers, twenty-three male kick boxers and twenty-three age-matched male were enrolled in the study. Health assessment data were analysed. Boxers and kick boxers underwent an exercise program including training plus fighting matches. Serum samples were collected in the pre- and post-exercise periods. Serum MA, BNP and copeptin concentrations were measured in these specimens using ELISA reagents. Results: comparative analysis of analytes before and after exercise showed that exercise significantly increased serum IMA, BNP and copeptin levels both in boxers and kick boxers. Conclusion: in conclusion, IMA, BNP and copeptin levels may be candidate biomarkers for exercise-related traumatic brain injuries. The identification of new biomarkers in patients with acute and chronic neurological disorders is of considerable interest to clinicians. Then, further studies should be conducted to evaluate the possible role of IMA, BNP and copeptin in TBI pothophysiology.
Keywords: Brain injuries; traumatic; exercise therapy; natriuretic peptide; brain; Myocardial-Ischemia; Cobalt-Binding; Injury; Biomarkers; Sports; Plasma; Marker